1986
DOI: 10.1136/oem.43.10.692
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relation of urinary phenol levels to breathzone benzene concentrations: a factory survey.

Abstract: Urine samples were collected from 64 men and 88 women in shoe factories and printing plants at the end of a seven hour day shift in the latter half of a week in spring. Urine samples were also taken from 43 men and 88 women in the same factories but who were not exposed to solvents. Exposure to benzene during the shift was monitored by passive dosimeters. Both phenol in urine and benzene in activated carbon were analysed with FID gas chromatographs. The urinary concentrations of phenol were linearly related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…The urinary concentrations of phenol and hydroquinone varied widely (ie 5-to 25-fold) within a given population. [49][50][51] Some studies have reported differences in phenol levels between sexes, 54 whereas others have not. 48 Variability of phenol levels among individuals appears to be greater than the difference among males and females.…”
Section: Phenol and Hydroquinone Levels In Unexposed Individualsmentioning
confidence: 99%
See 4 more Smart Citations
“…The urinary concentrations of phenol and hydroquinone varied widely (ie 5-to 25-fold) within a given population. [49][50][51] Some studies have reported differences in phenol levels between sexes, 54 whereas others have not. 48 Variability of phenol levels among individuals appears to be greater than the difference among males and females.…”
Section: Phenol and Hydroquinone Levels In Unexposed Individualsmentioning
confidence: 99%
“…), urinary phenol levels were seen as a good biomarker for exposure to benzene. [46][47][48] Studies, such as those conducted by Inoue et al, 49,50 observed a significant correlation between air concentration of benzene in breathing zone and phenol or hydroquinone concentrations in urine (corrected for creatinine and specific gravity) ( Figure 2). The authors reported a significant difference between urinary phenol levels in a group exposed to 10 p.p.m.…”
Section: Phenol and Hydroquinone Levels In Benzene-exposed Individualsmentioning
confidence: 99%
See 3 more Smart Citations